Perancangan Evaluasi Karyawan pada PT. X - Melisa Chan; I Nyoman Sutapa (Jurnal Titra, 2022)
Human Resource Development is a department that works in the field of legal documents and applies company regulations to employees. In addition, Human Resource Development also conducts evaluations for employees which are used to assess employee performance while working at a company. Every company has its own criteria and standards for assessing its employees and employee appraisal must be measurable by many criteria and must be balanced in its assessment between duties and responsibilities. PT. X has four assessment criteria, namely employee attendance, complying with company regulations, competence and cleanliness. Standards owned by the company must be specific according to employee competence and relevant to employee performance. Employee evaluation conducted by PT. X will be seen whether it is in accordance with the SMART method.